The heart goes last [compact disc, unabridged] : a novel - Atwood, Margaret, 1939- (Books on Tape, 2015)
"Stan and Charmaine are a married couple trying to stay afloat in the midst of an economic and social collapse. Job loss has forced them to live in their car, leaving them vulnerable to roving gangs. They desperately need to turn their situation around--and fast. The Positron Project in the town of Consilience seems to be the answer to their prayers. No one is unemployed and everyone gets a comfortable, clean house to live in...for six months out of the year."--